Protecting the Vulnerable: Child Custody Adjudication in Domestic Violence Cases in Banyuwangi Religious Court - Putri Maja Mulia Anisa; Tamam, Badrut; Alrawasdeh , Ziyad (Indonesian Journal of Islamic Law, 2024)
Domestic Violence (KDRT), which also often causes child custody disputes between two parents, is one of the many factors in divorce. Judges must consider the value of justice for each party when they decide a case. Building clear standards in assessing justice and dealing with social problems in the legal realm is difficult, especially when problems continue to arise in society, especially regarding child custody after divorce due to domestic violence. The method used in this research is empirical legal research, using legislative, conceptual, and legal psychology approaches. The results of this research are that the judge uses legal interpretation and legal principles based on Law Number 23 of 2002 article 2 letter b concerning Child Protection where"  the appropriate hadhanah must be based on the child's interests and by with the case being handled. If the father is at fault here then the judge must also refer to the provisions of KHI Article 105 where the custody of a child who has not yet mumayyiz will fall into the hands of the mother by using the civil law principle of proof (burden of proof), judges sometimes face external obstacles in the form of community participation in providing testimony regarding facts in the field, but if the facts and If the required evidence exists and all the interests of the child have been considered, the determination will be easier without any legal constraints or obstacles.